Passive Anti-amyloid Beta Monoclonal Antibodies: Lessons Learned over Past 20 Years - Alexandra Wicker; Jahnavi Shriram; Boris Decourt; Marwan Noel Sabbagh (Neurology and Therapy)
Abstract Alzheimer’s disease (AD) is a neurodegenerative disorder that significantly impairs cognitive and functional abilities, placing a substantial burden on both patients and caregivers. Current symptomatic treatments fail to halt the progression of AD, highlighting the urgent need for more effective disease-modifying therapies (DMTs). DMTs under development are classified as either passive or active on the basis of their mechanisms of eliciting an immune response. While this review will touch on active immunotherapies, we primarily focus on anti-amyloid beta monoclonal antibodies (mAbs), a form of passive immunotherapy, discussing their multifaceted role in AD treatment and the critical factors influencing their therapeutic efficacy. With two mAbs now approved and prescribed in the clinical setting, it is crucial to reflect on the lessons learned from trials of earlier mAbs that have shaped their development and contributed to their current success. These insights can then guide the creation of even more effective mAbs, ultimately enhancing therapeutic outcomes for patients with AD while minimizing adverse events.